Produção do capim mombaça (megathyrsus maximus) com adubação fosfatada única ou parcelada - Cardoso, Mara Régia de Sousa (Universidade Federal do Tocantins, 2021)
The objective of this study was to evaluate the effect of two phosphate fertilization strategies (single-AUP or split-APP) on the growth and productivity of Mombaça grass (Megathyrsus maximus). A completely randomized design was used, with repeated measures over time. Fertilization and evaluations were carried out every 21 days. The variables evaluated were: growth per cycle (CC), height growth rate (TCA), available dry mass (MSDisp), accumulated dry mass (MSAc), accumulation rate (TAc) and carrying capacity (CS). There was no interaction (p>0.05) of the strategy and cycle (Est. x C) for the analyzed variables. The AUP treatment presented higher CC, TCA, MSAc, TAc and CS when compared to the APP treatment. Significant differences were observed between cycles in the variables CC, TC, MSDisp and CS. The single phosphorus application strategy allowed for greater productivity per pasture area, which enabled an increase in stocking.